2017
DOI: 10.2486/indhealth.2016-0147
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of workplace air concentrations of formaldehyde during and before working hours in medical facilities

Abstract: Workplace air concentrations of formaldehyde (FA) in medical facilities where FA and FA-treated organs were stored and handled were measured before and during working hours and assessed by the official method specified by Work Environment Measurement Law. Sixty-percent of the total facilities examined were judged as inappropriately controlled work environment. The concentrations of FA before working hours by spot sampling were found to exceed 0.1 ppm in some facilities, and tended to increase with increasing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Additionally, we asked the workers not to block the ventilation systems. Another previous study reported that appropriate storage was effective for the reduction of formaldehyde concentrations in the workplace . Therefore, we also asked the workers not to keep the waste fluid tank open to prevent formaldehyde diffusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we asked the workers not to block the ventilation systems. Another previous study reported that appropriate storage was effective for the reduction of formaldehyde concentrations in the workplace . Therefore, we also asked the workers not to keep the waste fluid tank open to prevent formaldehyde diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…The work environment measurement system in Japan suggests that these assessments be conducted for two continuous days, if possible. If the work environment is measured in a day, the calculation formula taking the empirical between‐day variation into consideration is used; the evaluation of the workplace can be more severe if measured in a day, as there might be less between‐day variation in the continuous 2‐day measurements. Therefore, in order to assess the actual improvement, the work environment should be measured for two continuous days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within anatomy laboratories storage facilities have been identified as a location with high exposures. Higashikubo and co-workers [ 27 ] reported average pre-shift FA concentrations of 450 µg/m 3 in Japanese anatomy facilities and reported an increase of FA exposure with installed storage capacity. Leakage of loosely sealed containers was identified as the primary source of this background.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Union, instead, the number of workers exposed to FA above the background level is calculated to be 1.7 million, 175,380 of them in Italy [5] , [6] . Although most exposed workers are foreseeably engaged in chemical and plastics factories, the highest mean levels of exposure were actually recorded in the health-care sector [6] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%